Development of the Andalusian group identity - Apaydin, Marina (Revista de Estudios Andaluces, 2014)
Throughout its 700 years history, al-Andalus has consistently enjoyed an image of a "Paradise on Earth" in spite of its continuous internal economic, social and political problems and external threats. This paper attempts to uncover how the Andalusian group identity was formed, what its main characteristics were, why they were viewed as attractive and how this information was transmitted and maintained. The research for this study was conducted in 2005 in Southern Spain, which used to be al-Andalus. A combination of primary and secondary sources, and historical visual artifacts were used as a basis for this analysis. Theoretical grounding for this work was developed based on several social theories of Bourdieu, Ringrose, Piaget, Cavalli-Sforza and Maslow.